PERAN KEDOKTERAN FORENSIK DALAM PEMBUKTIAN PERKARA PIDANA - Reny Okprianti; Nur Husni Emilson; Syarifah Al Amiroh; Nikita Febriyani; Rina Oktarina; Wulan Purnama Sari (Collegium Studiosum Journal, 2025)
The relationship between law and medicine is crucial in the process of proving someone's guilt because not all aspects of knowledge can be mastered by a judge. In this case, the role of a doctor is vital in helping reveal the condition of evidence in the form of a human body or human body parts in a trial. The role of forensic doctors is very significant in handling criminal cases by revealing evidence that can be in the form of a human body or body parts, as well as providing an assessment of the causal relationship between the victim and the perpetrator of the crime through a post-mortem report, which provides an overview for the judge. Through their medical knowledge and forensic skills, forensic doctors help uncover facts related to criminal cases, especially in cases of death or physical violence. By conducting post-mortem examinations, autopsies, and preparing post-mortem reports, they provide medical evidence that is crucial for the investigation and criminal evidence process in court.